Pengaruh Budaya Organisasi dan Kepemimpinan Kewirausahaan terhadap Motivasi Karyawan dan Dampaknya pada Peningkatan Kinerja Organisasi (Studi Pada PT Industri Kereta Api/INKA Madiun) - Lisdiantini, Netty (Widya Warta, 2013)
The study was conducted to examine the influence of organizational culture and entrepreneurial leadership toward employees’ motivation and its impact on the improvement of organizational performance. The research was held at PT Industri Kereta Api (INKA) Jl. Yos Sudarso No. 71 Madiun. The sample was determined by census. The population is 81 persons. The primary data were obtained through questionnaires, while the secondary data were taken from the official documents of the organization and some relevant literature that supports the primary data.  This  study  made  use  of  survey.  To get the  sample,  the  main  data collection  tool, questionnaire, was applied. Due to its analysis, the study is classified as an explanatory research. The method of analysis applied includes path analysis, t-test, test coefficient of determination accompanied by classical assumption testing. The result of the data analysis showed that (1) organizational culture had positive and significant impact on entrepreneurial leadership, (2) organizational culture had positive and significant impact on employees’ motivation, (3) entrepreneurial leadership had a direct positive and significant impact on employees’ motivation, (4) organizational culture had a direct positive and significant effect on organizational performance, (5) entrepreneurial leadership had a direct positive and significant effect on organizational performance, and (6) employees’ motivation had a direct positive and significant impact on organizational performance.